2011
DOI: 10.1016/j.ccr.2011.05.027
|View full text |Cite
|
Sign up to set email alerts
|

miR-30b/30d Regulation of GalNAc Transferases Enhances Invasion and Immunosuppression during Metastasis

Abstract: Summary To metastasize, a tumor cell must acquire abilities such as the capacity to colonize new tissue and evade immune surveillance. Recent evidence suggests that microRNAs can promote the evolution of malignant behaviors by regulating multiple targets. We performed a microRNA analysis of human melanoma, a highly invasive cancer, and found that miR-30b/30d upregulation correlates with stage, metastatic potential, shorter time to recurrence and reduced overall survival. Ectopic expression of miR-30b/30d promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
299
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(315 citation statements)
references
References 50 publications
12
299
2
2
Order By: Relevance
“…We observed that a group of miRNAs were consistently expressed either at a high level (e.g., let7a/b, miR-21 and miR-30d, Figure 6) or a low level (e.g., miR-34b, miR-26a, miR-137, miR-18b). These results are consistent with previous reports of deregulation of future science group Methodology Chatterjee, Stockwell, Rodger, Parry & Eccles these miRNAs in melanoma [43][44][45][46][47][48]. Furthermore, a group of miRNA showed distinct expression profiles between primary and melanoma patients.…”
Section: Mirna Profiling Of Primary and Metastatic Melanoma Tumorssupporting
confidence: 92%
“…We observed that a group of miRNAs were consistently expressed either at a high level (e.g., let7a/b, miR-21 and miR-30d, Figure 6) or a low level (e.g., miR-34b, miR-26a, miR-137, miR-18b). These results are consistent with previous reports of deregulation of future science group Methodology Chatterjee, Stockwell, Rodger, Parry & Eccles these miRNAs in melanoma [43][44][45][46][47][48]. Furthermore, a group of miRNA showed distinct expression profiles between primary and melanoma patients.…”
Section: Mirna Profiling Of Primary and Metastatic Melanoma Tumorssupporting
confidence: 92%
“…Moreover, some diagnostic miRNAs can be used in therapy. For instance, in previous studies, miR-155, which is downregulated in melanoma, was injected in melanoma cell lines to increase its expression (1,21,22). Similar procedures can be executed for miR-193b as a practical therapeutic option (1).…”
Section: Discussionmentioning
confidence: 99%
“…This gene modifies the cell surface of melanoma cells and affects cellular adherence; metastasis occurs due to discontinuity of cancerous cells. Therefore, miR-30b and miR-30 are accountable for metastasis in melanoma (1,21,22).…”
Section: Immunosuppressive Mirnasmentioning
confidence: 99%
“…In addition to the increased metastatic potential, the upregulation of these miRNAs correlates with shorter time to recurrence and reduced overall survival. Overexpression of miR-30b/30d promotes melanoma metastasis by modifying the glycosylation pattern of transmembrane proteins, more specifically by directly repressing GalNAc transferase GALNT7, which culminates in pro-invasive and immunosuppressive effects [120].…”
Section: Micrornasmentioning
confidence: 99%